Association between fundamental motor skills and physical activity in the early years: A systematic review and meta-analysis - Dan Jones; Alison Innerd; Emma L. Giles; Liane B. Azevedo (Elsevier, 2020)
Background: Physical activity (PA) in the early years is associated with a range of positive health outcomes. Fundamental motor skill (FMS) competence is associated with PA and is theorized to be driven by PA in the early years and vice versa in mid to late childhood. However, to date, no studies have meta-analyzed the association between PA and FMS in the early years. Methods: Six electronic databases were searched for articles published up to April 2019. Cross-sectional and longitudinal studies were included if they targeted children (ages 3-6 year) as the population of the study and assessed the association between objectively measured PA and FMS. Total FMS, total physical activity (TPA), and moderate-to-vigorous physical activity (MVPA) data were meta-analyzed using a random effects model. Results: We identified 24,815 titles and abstracts. In total, 19 studies met the inclusion criteria, including 14 cross-sectional and 4 longitudinal studies, as well as 1 study with cross-sectional and longitudinal analysis. There was a significant but small positive association between FMS and MVPA (r = 0.20, 95% confidence interval (CI): 0.13-0.26) and TPA (r = 0.20, 95%CI: 0.12-0.28). Findings from longitudinal studies revealed that PA drives FMS in early childhood. Mediation was explored in 1 study, which found that perceived motor competence did not mediate the association between FMS and PA. Conclusion: Using a meta-analysis, this study is the first to show a positive association between FMS, MVPA, and TPA in the early years of childhood, suggesting that the association begins at an early age. Limited evidence from longitudinal studies supports the theory that PA drives FMS in the early years of childhood. More evidence is needed from large studies to track PA and FMS until mid to late childhood and to explore the mediators of this association.